A qualitative analysis of rural syringe service program fidelity in Appalachian Kentucky: Staff and participant perspectives. Issue 2 (18th September 2022) - Batty, E.J.; Ibragimov, U.; Fadanelli, M.; Gross, S.; Cooper, K.; Klein, E.; Ballard, A. M.; Young, A. M.; Lockard, A. S.; Oser, C. B.; Cooper, H. L. F.
Abstract: Purpose: As drug‐related epidemics have expanded from cities to rural areas, syringe service programs (SSPs) and other harm reduction programs have been slow to follow. The recent implementation of SSPs in rural areas demands attention to program fidelity based on core components of SSP success. Methods: Semistructured interviews conducted with clients and staff at 5 SSPs in 5 counties within 2 Central Appalachian health districts. Interviews covered fidelity of SSP implementation to 6 core components: (1) meet needs for harm reduction supplies; (2) education and counseling for sexual, injection, and overdose risks; (3) cooperation between SSPs and local law enforcement; (4) provide other health and social services; (5) ensure low threshold access to services; and (6) promote dignity, the impact of poor fidelity on vulnerability to drug‐related harms, and the risk environment's influence on program fidelity. We applied thematic methods to analyze the data. Findings: Rural SSPs were mostly faithful to the 6 core components. Deviations from core components can be attributed to certain characteristics of the local rural risk environment outlined in the risk environment model, including geographic remoteness, lack of resources and underdeveloped infrastructure, and stigma against people who inject drugs (PWID) Conclusions: As drug‐related epidemics continue to expand outside cities, scaling up SSPs to serve rural PWID is essential. Future research should explore whether the risk environment features identified also influence SSP fidelity in other rural areas and develop and test strategies to strengthen core components in these vulnerable areas.